FUNCTIONAL ACCOUNTING EDUCATION CURRICULUM FOR SUSTAINABLE YOUTH ENTREPRENEURSHIP - Ahmed Oluwatobi Adekunle (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2025)
Companies that are always looking for methods to save expenses and stay competitive have made professionalism in accounting education a priority. Thus, the type of professionals that are in need today must be produced by the accounting education that students receive. Redundancies, gaps in the accounting curriculum, and a lack of financial and human resources to make meaningful improvements are some of the factors contributing to the shortage of workers with the necessary skills and capacity. Sequel to this, this study aims at examining functional accounting education curriculum for sustainable youth empowerment. The study's participants were employees of the Edo State Ministry of Education; 45 employees in total were selected from the population, which was used to calculate the sample size. The study used a survey research design, and the findings indicate that the functional education curriculum has little impact on long-term youth empowerment in Edo State. The study suggests that the Nigerian University Commission create a workable curriculum that will encourage accounting education among young people by creating jobs.